Historical stages in the formation of the scientific knowledge system in a theoretical and methodological context - Griffen, Leonid; Ryzheva, Nadiia; Nefodov, Dmytro; Hryashchevskaya, Lyudmila (Linguistics and Culture Review, 2021)
Current tendencies question the role of science in modern society, force returning to the processes of formation of the scientific paradigm. The latter was complex and nonlinear, and the formation of scientific principles of cognition was their natural result. Throughout human history, the knowledge about the objective world has been acquired and used in various, historically necessary forms – both in the methodology of cognition and in the method of systematisation, which was determined by the level of their accumulation. The accumulation of knowledge took place in different ways: in the process of direct practical activity, on the basis of supposedly “foreign” contemplation and as a result of conscious influence on an object of study (experiment) with their different “specific weight” at different historical stages. As for the systematisation, the need for which was determined by systemic nature of an object of knowledge and the social nature of knowledge, throughout the history of mankind its forms differed considerably, but, in the end, were reduced to three main ones.